MRI-derived g-ratio and lesion severity in newly diagnosed multiple sclerosis. Issue 4 (3rd November 2021) - York, Elizabeth N; Martin, Sarah-Jane; Meijboom, Rozanna; Thrippleton, Michael J; Bastin, Mark E; Carter, Edwin; Overell, James; Connick, Peter; Chandran, Siddharthan; Waldman, Adam D; Hunt, David P J; ,
Abstract: Myelin loss is associated with axonal damage in established multiple sclerosis. This relationship is challenging to study in vivo in early disease. Here, we ask whether myelin loss is associated with axonal damage at diagnosis by combining non-invasive neuroimaging and blood biomarkers. We performed quantitative microstructural MRI and single-molecule ELISA plasma neurofilament measurement in 73 patients with newly diagnosed, immunotherapy naïve relapsing–remitting multiple sclerosis. Myelin integrity was evaluated using aggregate g-ratios, derived from magnetization transfer saturation and neurite orientation dispersion and density imaging diffusion data. We found significantly higher g-ratios within cerebral white matter lesions (suggesting myelin loss) compared with normal-appearing white matter (0.61 versus 0.57, difference 0.036, 95% CI: 0.029–0.043, P < 0.001). Lesion volume (Spearman's rho rs = 0.38, P < 0.001) and g-ratio (rs = 0.24, P < 0.05) correlated independently with plasma neurofilament. In patients with substantial lesion load ( n = 38), those with higher g-ratio (defined as greater than median) were more likely to have abnormally elevated plasma neurofilament than those with normal g-ratio (defined as less than median) [11/23 (48%) versus 2/15 (13%), P < 0.05]. These data suggest that, even at multiple sclerosis diagnosis, reduced myelin integrity is associated with axonal damage. MRI-derived g-ratio may provide useful additional information regarding lesion severity and help to identify individuals with a high degree of axonal damage at disease onset. Abstract : York et al. simultaneously measured g-ratio and plasma neurofilament in 73 relapsing–remitting multiple sclerosis patients at diagnosis using advanced MRI and single-molecule ELISA. They demonstrate that g-ratio of cerebral white matter lesions varies at diagnosis, and show that high g-ratio of lesions is associated with elevated plasma neurofilament. Graphical Abstract: